PERLINDUNGAN HAK CIPTA BAGI PENCIPTA SENI LUKIS DIGITAL DALAM TRANSAKSI JUAL BELI NON-FUNGIBLE TOKEN - Fikri Setyo Arief Pambudi; Krisnadi Nasution (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
At this moment, the development of the era are getting faster and more advanced, where these developments also impact on human’s daily activities. One of the developments is the media that displayed through digital technologies. This development also has an impact on the field of arts, which is now not only poured onto canvases using painting tools and other equipments generally used to painting, but also poured into digital media. This digital artwork is not only created for aesthetic purposes, but also as an object for business transactions and investments. This digital artwork is known as NFT (Non-Fungible Token). Howeer, on the other hand, digital artwork also risked their creators, such as copyright issues due to the convenience to access the digital artwork through the internet. This convenience also creates the possibility for reseller to resell the digital artwork after purchasing the art from its creator. In fact, the creator of the digital artwork is the one who owns the copyright to the artwork, so reseller have no right to resell the artwork unless they have agreement about that. If the reseller or other party involved in the copyright violation or violate the agreement, the creator of the digital artwork has the right to be protected by the law enforcement. Based on that problem, the writer conducted thi research to find out the efforts to regulate copyright protection for digital artwork’s creator in NFT business transactions. This research provides a visualization of the reality that occurs, through data collection called analytical descriptive research. The result of this research state that there is a legal relationship between digital artwork’s creator and the buyer or resellers, which is established when these parties are agree to involved in business transaction, that also stated in Pasal 1233, Pasal 1234, and Pasal 1131 KUHPerdata. Copyright legal protection for digital artwork’s creators also stated internationally in the Berne Convention which states that, “every work has received automatic protection since the creation became real (realexpression), protection is given directly without depending on the creator's country of origin (direct and independent protection), and the application of this provision applies equally to all countries that have ratified the Berne Convention, including WTO member countries that have also signed the TRIPS Agreement